Reshaping the university : responsibility, indigenous epistemes, and the logic of the gift - Kuokkanen, Rauna Johanna (desLibris. Books collection., 2007)
"In the past few decades, the narrow intellectual foundations of the university have come under serious scrutiny. Previously marginalized groups have called for improved access to the institution and full inclusion in the curriculum. Reshaping the University is a timely, thorough, and original interrogation of academic practices. It moves beyond current analyses of cultural conflicts and discrimination in academic institutions to provide an indigenous postcolonial critique of the modern university." "Rauna Kuokkanen argues that attempts by universities to be inclusive are unsuccessful because they do not embrace indigenous worldviews. Programs established to act as bridges between mainstream and indigenous cultures ignore their ontological and epistemic differences and, while offering support and assistance, place the responsibility of adapting wholly on the student. Indigenous students and staff are expected to leave behind their cultural perspectives and epistemes in order to adopt Western values. Reshaping the University advocates a radical shift in the approach to cultural conflicts within the academy and proposes a new logic; grounded in principles central to indigenous philosophies."--Jacket